Measurement of heat capacity and thermal conductivity of HDPE/expanded graphite nanocomposites by differential scanning calorimetry - Tavman, I.; Aydogdu, Y.; Kök, M.; Turgut, A.; Ezan, A. (My University, 2011)
Purpose: In this study, heat capacity and thermal conductivity of nanocomposites formed by high density polyethylene (HDPE) matrix and expanded graphite (EG) conductive filling material were investigated. Design/methodology/approach: Nanocomposites containing up to 20 weight percent of expanded graphite filler material were prepared by mixing them in a Brabender Plasticorder. Two grades of expanded graphite fillers were used namely expanded graphite with 5 ?m (EG5) and 50 ?m (EG50) in diameter. Heat capacity and thermal conductivity of pure HDPE and the nanocomposites were measured using differential scanning calorimetry (DSC). Findings: A substantial increase in thermal conductivity was observed with the addition of expanded graphite to HDPE. Thermal conductivity increased from 0.442 W/m.K for pure HDPE to 0.938 W/m.K for nanocomposites containing 7% by weight of expended graphite. Heat capacity increases with the increase in temperature for both pure HDPE and the nanocomposites filled with expanded graphite and no appreciable difference in the values of heat capacity were detected due to particle size. Heat capacity decreased with increasing graphite particle content for both particle size, following the low of mixtures. Practical implications: Layers of expanded graphite have become of intense interest as fillers in polymeric nanocomposites. Upon mixing the expanded graphite intercalates and exfoliates into nanometer thickness sheets due to their sheet-like structure and week bonds normal to the graphite sheets. That way they have very big surface area and high aspect ratio (200-1500) what results in a formation of percolating network at very low filler content. The nanoparticles usage results in significant improvement in thermal, mechanical, and electrical properties of polymers even with very low loading levels compared with microparticles. Originality/value: To see the effect of conducting fillers on thermal conductivity and heat capacity two different sizes of expanded graphite were used. © International OCSCO World Press.
Keywords: Conductive nanocomposites; Expanded graphite; HDPE; Heat capacity; Thermal conductivity